Problem Solving For Better Health (PSBH) Rendam Kaki Air Hangat dengan Serai pada Penderita Hipertensi - Doni Bilman Murizki; Amnaria Maretha; Fitrian Fitrian; Helwati Mursyida; Reza Rizki Amaliyah; Sri Nopita Sari; Verawanty Verawanty; Julianto Julianto (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
Hypertension is a global health issue that requires holistic management, including non-pharmacological therapies. This community service activity aimed to educate and assist residents of Pekauman RT 07 in applying warm foot soak therapy with lemongrass as an alternative method to reduce blood pressure. The implementation method used a participatory approach involving observation, education, direct practice, and pre-post intervention evaluation. The results showed that most participants experienced a decrease in blood pressure after the intervention. This therapy is considered simple, safe, and feasible to perform independently at home. The program is expected to continue as a community empowerment strategy in hypertension management.